2010
DOI: 10.1111/j.1439-0426.2010.01429.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the appearance of skeletal anomalies in red porgy: effect of culture intensiveness, feeding habits and nutritional quality of live preys

Abstract: Despite the great interest of red porgy as a new species for Mediterranean aquaculture, its commercial production is constrained by the high incidence of skeletal deformities occurring in this species under culture conditions. Several studies have been conducted to better understand the origin of these anomalies in this species, using different system intensiveness, rotifers enrichment products or rotifers docosahexaenoic acid content. The first study showed that culture intensification increased the number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 68 publications
(98 reference statements)
4
58
1
3
Order By: Relevance
“…Hamre et al (2002) suggested that the abnormal development of fish larvae may be triggered by insufficient dietary n-3 HUFA in Artemia nauplii. Recent evidence has demonstrated that fatty acids such as DHA, EPA and ARA play important role in bone development and a 50% reduction of deformed fish was observed when fish larvae were fed with higher levels of dietary DHA (Izquierdo et al, 2010). In the present study, incidence of skeletal malformation was lower in the treatment of Algamac 3080 which is consistent with high DHA levels in the feeds.…”
Section: P<005)supporting
confidence: 77%
“…Hamre et al (2002) suggested that the abnormal development of fish larvae may be triggered by insufficient dietary n-3 HUFA in Artemia nauplii. Recent evidence has demonstrated that fatty acids such as DHA, EPA and ARA play important role in bone development and a 50% reduction of deformed fish was observed when fish larvae were fed with higher levels of dietary DHA (Izquierdo et al, 2010). In the present study, incidence of skeletal malformation was lower in the treatment of Algamac 3080 which is consistent with high DHA levels in the feeds.…”
Section: P<005)supporting
confidence: 77%
“…Jaw malformations are a common type of skeletal malformation and exhibit in several forms (Cobcroft et al 2001) in both artificial reared and wild caught marine fish (Boglione et al 2001). Izquierdo et al (2010) suggest that PUFA is important in bone formation, and dietary lipids can also affect the fatty acid composition in bone and cartilage (Kokkinos et al 1993;Watkins et al 1997;Liu et al 2004). Hamre et al (2002) suggests that the abnormal development of fish larvae may be triggered by insufficient dietary n-3 HUFA in Artemia nauplii.…”
Section: Discussionmentioning
confidence: 97%
“…Recent research has demonstrated that fatty acids such as DHA, EPA, and ARA play an important role in bone development. For instance, a 50 % reduction in deformed fish was observed when fish larvae were fed with higher levels of dietary DHA (Izquierdo et al 2010), and alterations in the dietary ARA/EPA ratio can indirectly affect osteoblasts and bone metabolism (Berge et al 2009). In the present study, enrichment significantly affected jaw malformation.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Entre las causas a las que se ha asociado la aparición de malformaciones esqueléticas se encuentra la intensificación de los cultivos, condiciones abióticas desfavorables, desbalances nutricionales, enfermedades y factores genéticos (Andrades et al, 1996;Cahu et al, 2003;Fraser & de Nys, 2005;Georgakopoulou et al, 2007;Verhaegen et al, 2007;Izquierdo et al, 2010). El objetivo de la presente revisión bibliográfica, es resumir la información existente sobre las características y las causas de las malformaciones craneales en larvas de peces cultivados.…”
Section: Introductionunclassified